ANALYSIS OF THE PERFORMANCE EFFECTIVENESS OF CONVENTIONAL BANKS COMPARED TO ISLAMIC BANKS - Meilyana, Elyssa; Arif Alauddin Okta Saputra; Mella Saputri; Elsa Putri Pratama; Dimi; Annisa Mutohharoh; Kevin Jexi Levi (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2023)
Indonesia occupies the first position of the country with the most Muslim majority in the world. The population of the Muslim community in the country is equivalent to 86.7% of the total population in Indonesia. However, it turns out that conventional banks are still the superior choice for the Indonesian Muslim community for various financial transactions or services compared to Islamic banks. Banks are financial organizations or companies that are close friends with the community, these two things are interdependent and need each other. From the title listed, of course we already know about conventional economics. The target to be achieved in this research is to find out whether there are special advantages or dissimilarities between these idealistic banks and Islamic banks, starting from the function of offering services and financial regulations. Here the researcher uses the literature study method. Conventional banks really spoil their customers by providing a number of tempting benefits, for example, getting interest from deposits that are deposited. But on the other hand, conventional banks led to the wrong path, namely usury, then the Indonesian Ulema Council (MUI) Banking issued the oldest sharia bank in this country, namely Bank Muamalat Indonesia. People still consider these two things. Keywords: Muslim, conventional banks, Islamic banks